The restriction-modification system in Streptomyces flavopersicus - Lyutzkanova, D; Stoilova-Disheva, M; Peltekova, V (Folia microbiologica, 2001)
To clone bifunctional vectors in streptomycetes, it was necessary to define the restriction-modification system of Streptomyces flavopersicus. Plasmid DNA from bifunctional vectors pIJ699 and pXED3-13, isolated from E. coli strains with different methylation systems: E. coli DH5 alpha (dam+ dcm+), E. coli MB5386 (dam dcm), E. coli CB51 (dam dcm+), E. coli NM544 (dam+ dcm), was used for transformation of protoplasts from strain S. flavopersicus. Restriction of dcm-methylated DNA from S. flavopersicus was established. As a host in the intermediate cloning strain E. coli NM544 (dam+ dcm) should be used, as the dcm-transmethylase-dependent strain S. flavopersicus does not process DNA from this strain.
Keywords: DNA restrikčně-modifikační enzymy; plazmidy; klonování DNA; DNA Methylation; DNA, Recombinant; Transformation, Genetic; Plasmids; rekombinantní DNA; transformace genetická; Escherichia coli; metylace DNA; DNA Restriction-Modification Enzymes; Streptomyces; Cloning, Molecular